Estratégias de somação temporal e espacial na formação da memória declarativa de curto prazo - Marques, Jean Felipe; Barros, Rafael Fernandes; Santos, Rafael Peres dos; Pereira Júnior, Alfredo [UNESP] (My University, 2012)
In this essay, we analyze the formation of short-term declarative memory under conditions which correspond to temporal and spatial summation. We presented to four groups of university students a sequence of slides, with the duration of 7 seconds each, containing sentences (one for each slide) that could be of greater or lesser interest to them. There was a total of 25 sentences, of which 5 were repeated three times, and the remaining 10 sentences were presented randomly only once. After presenting the sentences, the subjects answered a written questionnaire about each one of them. Analyzing the answers, we found that the repeated sentences eliciting temporal summation were on average more efficacious to form short-term memories, but some of the sentences presented just one time were more remembered than sentences presented three times. This result suggests that spatial summation may be more efficient to form such memories, if the stimulus and the form of presentation are sufficiently powerful to elicit a variety of converging learning pathways for the subjects.

Neste trabalho, estudamos a formação de memória declarativa de curto prazo em condições que correspondem a processos de somação temporal e espacial. Apresentamos para alunos universitários uma sequência de slides, com duração de sete segundos cada, contendo sentenças (uma por slide) que poderiam ser de maior ou menor interesse para os sujeitos. Ao todo foram apresentadas 25 sentenças, das quais cinco repetidas três vezes e as 10 restantes apresentadas apenas uma vez, intercaladas aleatoriamente. Após a apresentação, os sujeitos responderam a questões referentes a cada sentença. Verificamos que as sentenças apresentadas três vezes apresentaram, em média, maior número de respostas corretas, indicando uma eficácia da estratégia de aprendizagem baseada na somação temporal. Contudo, também verificamos que a sentença mais lembrada foi apresentada apenas uma vez, e que outras seis sentenças apresentadas apenas uma vez obtiveram maior número de respostas corretas que a média das sentenças apresentadas três vezes, o que indica a possibilidade de maior eficiência das estratégias de somação espacial.
Keywords: Memory; Learning; Temporal summation; Spatial summation; Repetition; Relevance; Memória; Aprendizagem; Somação temporal; Somação espacial; Repetição; Relevância